Target strengths and echotraces of whales and seals in the Canadian Beaufort Sea. (13th October 2015) - Geoffroy, Maxime; Rousseau, Shani; Knudsen, Frank Reier; Fortier, Louis
Abstract: Active acoustics as a tool to detect and avoid Arctic marine mammals was assessed in the Canadian Beaufort Sea. The target strengths and shape of the echoes of whales and seals were characterized using a bi-frequency (38 and 120 kHz) split-beam scientific echosounder in winter 2003/2004 and a scientific scanning sonar (20–30 kHz) in summer 2011. The echosounder detected 452 signals of diving ringed seals and the sonar detected 59 bowhead whales, 13 ringed seals, and 2 bearded seals. Target strengths of diving ringed seals tracked by the echosounder ranged from −56 to −12 dB re: 1 m 2 and did not vary with the depth of the animal. Target strengths of animals tracked by the sonar varied from −15 to 10 dB for bowhead whales and from −37 to −3 dB for seals. Marine mammals presented higher target strength values near broadside than near tail- or head-on. The sonar detected whales at a distance up to 2000 m and their echoes were discriminated from that of seals. This study suggests that active acoustic technology can be used as a complementary tool for marine mammal surveys in the Arctic.